Antiretroviral treatment outcomes and survival pattern of people living with HIV in Bauchi State, Nigeria - Ekerette Emmanuel Udoh; Adesola Zaidat Musa; Tubosun Alex Olowolafe; Chima Orakwe Obi; Oluwole Fajemisin; Taiwo Mofadeke Jaiyeola (PLoS ONE, 2025)
Background Antiretroviral therapy (ART) has greatly improved the survival and quality of life for individuals living with HIV. However, challenges in the prevention of HIV-related mortality and poor retention of patients in ART treatment pose threats to effective ART interventions. This study investigated the incidence, prevalence of ART outcomes, and survival pattern of persons living with HIV (PLHIV) on ART treatment in Bauchi state Nigeria. Methods A retrospective cohort study was conducted to investigate antiretroviral treatment outcomes in a sample of 5,608 HIV-positive persons from two clinics over 3 years from 1st January 2020–31st December 2022. Data was extracted from an electronic medical record (EMR) from treatment facilities, and analyzed to assess the incidence and survival function estimates for ART outcomes including interruption in treatment, lost-to-follow-up (LTFU), mortality, and viral load suppression. Patient baseline demographic characteristics, clinic, pharmacy, and laboratory data were also extracted to examine associations with ART survival outcomes. Descriptives statistics were used to summarize all variables. Meanwhile, to analyze the temporal-trend plot of incidence over the study years, the data were modeled using a Generalized Linear Model (GLM) with a Poisson distribution. Kaplan-Meier survival function plots were used to estimate the survival probability of treatment outcomes, while Cox proportional hazard was modeled to identify independent predictors of survival. Results The incidence of treatment interruption decreased steadily over the three years from 33.33 per 100 person-years (PY) in 2020 to 27.23 per 100PY in 2022. LTFU was shown to be low, decreasing significantly from 20.37 per 100PY in 2020 to 0.69 per 100PY in 2022. Incidence of mortality showed a reducing trend and ranged from 27.78 per 100PY in 2020 to 0.81 per 100PY in 2022. The high incidence observed for viral load suppression reduced slightly for the period of observation from 98.15 per 100PY to 89.62 per 100PY. Survival curves from survival analysis showed a generally decreasing survival probability trend on ART treatment outcomes, indicating a reduced risk of events over time. Additionally, participants with viral loads less than 1000 copies/ml had significantly reduced hazards of loss to follow-up (HR = 0.14, 95% CI: 0.06–0.33, p < 0.001) and death (HR = 0.26, 95% CI: 0.10–0.64, p = 0.003) compared to those with higher viral loads. Based on nutritional status of participants, overweight participants (HR = 0.07, 95% CI: 0.01–0.36, p = 0.001), as well as those with normal BMI (HR = 0.42, 95% CI: 0.18–0.98, p = 0.004) had a significantly reduced hazard of mortality compared with underweight participants. Conclusion This study demonstrated improvements in HIV treatment outcomes. However, health challenges which limit optimal ART outcomes require targeted interventions. The study highlights the importance of integrated care and support systems for optimal treatment and survival.